Updated Italian recommendations for the diagnosis, treatment and follow‐up of the first febrile urinary tract infection in young children. (6th October 2019) - Ammenti, Anita; Alberici, Irene; Brugnara, Milena; Chimenz, Roberto; Guarino, Stefano; La Manna, Angela; La Scola, Claudio; Maringhini, Silvio; Marra, Giuseppina; Materassi, Marco; Morello, William; Nicolini, Giangiacomo; et al.
Abstract: Aim: Our aim was to update the recommendations for the diagnosis, treatment and follow‐up of the first febrile urinary tract infection in young children, which were endorsed in 2012 by the Italian Society of Pediatric Nephrology. Methods: The Italian recommendations were revised on the basis of a review of the literature published from 2012 to October 2018. We also carried out an ad hoc evaluation of the risk factors to identify children with high‐grade vesicoureteral reflux or renal scarring, which were published in the previous recommendations. When evidence was not available, the working group held extensive discussions, during various meetings and through email exchanges. Results: Four major modifications have been introduced. The method for collecting urine for culture and its interpretation has been re‐evaluated. We have reformulated the algorithm that guides clinical decisions to proceed with voiding cystourethrography. The suggested antibiotics have been revised, and we have recommended further restrictions of the use of antibiotic prophylaxis. Conclusion: These updated recommendations have now been endorsed by the Italian Society of Pediatric Nephrology and the Italian Society for Pediatric Infectivology. They can also be used to compare other recommendations that are available, as a worldwide consensus in this area is still lacking. Abstract :